2009
DOI: 10.1007/s11207-009-9367-0
|View full text |Cite
|
Sign up to set email alerts
|

In situ Observations of CIRs on STEREO, Wind, and ACE During 2007 – 2008

Abstract: During the 2007 and 2008 solar minimum period, STEREO, Wind, and ACE observed numerous Corotating Interaction Regions (CIRs) over spatial separations that began with all the spacecraft close to Earth, through STEREO separation angles of ∼ 80 degrees in the fall of 2008. Over 35 CIR events were of sufficient intensity to allow measurement of He and heavy ion spectra using the IMPACT/SIT, EPACT/STEP and ACE/ULEIS instruments on STEREO, Wind, and ACE, respectively. In addition to differences between the spacecraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 30 publications
5
52
0
Order By: Relevance
“…Considering the rotation rate of the Sun, and the longitudinal separation between the spacecraft, this means that there is variability on the time scale of 1.5 -2 days. CIR observations at different spacecraft have been compared by Mason et al (2009) and more specifically in reference to STEREO observations (Leske et al, 2008) and Wind observations (Sanderson et al, 1998). These authors also noted that features present in in-situ data from one spacecraft are not always observed when one would expect at another spacecraft with an angular separation, as noticed here.…”
Section: Cir Periodicity and Predicted Arrival Timesmentioning
confidence: 62%
See 1 more Smart Citation
“…Considering the rotation rate of the Sun, and the longitudinal separation between the spacecraft, this means that there is variability on the time scale of 1.5 -2 days. CIR observations at different spacecraft have been compared by Mason et al (2009) and more specifically in reference to STEREO observations (Leske et al, 2008) and Wind observations (Sanderson et al, 1998). These authors also noted that features present in in-situ data from one spacecraft are not always observed when one would expect at another spacecraft with an angular separation, as noticed here.…”
Section: Cir Periodicity and Predicted Arrival Timesmentioning
confidence: 62%
“…There are, of course, some factors to keep in mind when considering these results. From the observations presented in the previous sections, it is apparent that during the period under study, solar-wind source regions on the solar surface can last for multiple solarrotation periods; however, a given source does not eject material with constant properties on time scales of even a few days, in agreement with Mason et al (2009). This suggests possible sources of error in solar-wind analysis techniques that assume a constant propagation speed over the entire CIR.…”
Section: Discussionmentioning
confidence: 81%
“…Kirk et al (2009) stated that the north and south polar-hole areas were reduced by ≈ 15 % in 2007 compared with 1996. Mason et al (2009) found that during the recent Minimum 23/24 in comparison with the previous one (22/23) there were many more co-rotating interaction regions observed, connected with the existence of more high-speed streams of solar wind. Moreover, a low solar-wind dynamic pressure, ≈ 40 % in comparison with the previous minimum, was observed (Mewaldt et al, 2010) and this was caused by the drop in the average proton density, which was ≈ 5.5 cm −3 , being less dense in comparison with the previous three minima by ≈ 70 % (Jian, Russell, and Luhmann, 2011).…”
Section: Introductionmentioning
confidence: 71%
“…Other effects may be important including the merging of CIRs in the outer heliosphere, the latitudinal extent of the CIR shocks (Richardson et al, 1993), and the connection to the CIR (Mason et al, 2009). The tendency for the higher peak intensities associated with the recurrent CIRs was seen in a survey by Mason et al (2008a) and Richardson et al (1993).…”
Section: Cir2 Eventmentioning
confidence: 97%
“…wind plasma and magnetic field parameters measured by the PLASTIC instrument and the magnetometer sensor. Both of those events are included in the survey of Mason et al (2009).…”
Section: Observationsmentioning
confidence: 99%